THE ROLE OF SAND ART IN PROMOTING PERSONAL CREATIVITY - Khachibabyan , S. S. (Modern Psychology, 2019)
This article is devoted to analysis of creativity, as the essence, structure, and main characteristics of the integral quality of a person, within the context of historical development of the subject studies. The main highlights were made based on the understanding of humanitarian orientation, as well as on the scientific approaches to multifunctional theory of creativity which has been up-to-date in recent decades. The article specifically focuses on the promotion of separate characteristics of creativity as a way of activating creative potential, and for more illustrative purposes thereof the article covers a functional model developed by us to promote creativity. The article also touches upon the issue of ways of promoting creativity, and within such context a new and unique method of painting is preseneted - sand art. Scientific studies on the sand art as a tool of psychological work are not known yet, which makes our work more relevant.The article provides a detailed analysis of the typical features of sand art which aims to justify the capabilities of this art to promote creativity characteristics.
Keywords: Creativity, creative potential, creativity characteristics, promotion, sand art.